The Senses of the World Art Confronting Data (Itinera, 2025)
The current era is characterized by the production of vast amounts of data across all sectors of society. This is made possible by ubiquitous technologies that can collect data from every human and non-human entity on the planet, as well as any environmental phenomena. Artistic practice offers a suitable platform for the endeavour to isolate specific expressive and signifying features from this indistinct mass of data. This paper focuses on a relatively overlooked field of research, where technology interacts with abstract data to extract what I propose to define as their “aesthetic sense”. Such an expression addresses the peculiar dynamics enabling art to move beyond the purely informative function of data, towards a different goal – designing experiences that turn the audience into perceptive participants, engaged in the otherwise imperceptible events and relations that are recorded and communicated by data. Technologies thus become media of polyphonic expression, able to give voice to other ways of feeling and being in the world. Emerging through computation is a sort of feeling that permeates the entire fabric of reality, of which any entity in the universe can become the protagonist. As a result, art stands out as a privileged gateway to a particular experience of reality. This kind of experience will be theoretically analysed in the present essay starting from the philosophy of Alfred North Whitehead, specifically from his notion of “feeling”.